Racing Heroes and Grieving Widows: A Study of the Representation of Death in Motorsport - Demers, Jean-Simon (Université d'Ottawa / University of Ottawa, 2018)
Gilles Villeneuve, Ayrton Senna, Greg Moore, Dale Earnhardt. Only four of a number of high-profile race car drivers to have lost their lives taking part in events at the highest levels of motorsport. The aim of the present study is to analyze the coverage of death in high-level motorsport in the printed sports news of La Presse and The Toronto Star in Canada for the 1982 to 2017 period inclusively. Mobilizing the existing literature on risk-taking, namely Lyng’s concept of edgework, as well as Hall’s work on representation, a thematic analysis of a sample of sports news articles (N=488) was conducted. Three main themes emerged from the analysis. The discussion surrounding motorsport fatalities revolved around the individual (the deceased driver), the social aspect of the death (primarily the family members left behind), and journalistic practices (how to cover death). In conclusion, the coverage of death in motorsport was found to be an instance where the athlete is heroized and sometimes revered even decades after their death. In this aspect, the figure of Gilles Villeneuve remains pivotal to motorsport discussions in Canada, even to this day. It also was found that sports journalists, through their coverage of deadly accidents, enact the traditional roles of the journalist in offering social criticism of their subject matter to their readers, and that motorsport drivers enact a highly specific type of masculinity when practicing their sport.
Keywords: Risk; Representation; Masculinity; Death; Sports journalism